2019
DOI: 10.1002/bab.1727
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of callus growth and secondary metabolites in different Thymus species and Zataria multiflora micropropagated under ZnO nanoparticles stress

Abstract: Thymus species are aromatic plants with diverse applications in food industries and medicine. This study was conducted to evaluate the potential effect of ZnO nanoparticles (NPs) on callus proliferation and thymol and carvacrol production in three Thymus species, that is, T. vulgaris, T. daenensis, and T. kotschyanus, and Zataria multiflora. For this purpose, callus induction was performed on Murashige and Skoog (MS) medium containing different plant growth regulators (PGRs). After optimization of callus growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…On the other hand, BITC accumulation slightly increased in callus treated with 2 mg/l SiO 2 NPs for 45 days, while no changes were observed in 30-day-old callus treated with the same NP concentration. Similar findings were reported for the accumulation of thymol and carvacrol in thyme callus stressed with different concentrations of ZnO NPs [37]. By comparing the growth of callus with the accumulation of BITC, it was observed that due to the application of NPs at different concentrations, Fe 3 O 4 NPs at both concentrations and SiO 2 at 0.5 mg/l decreased the callus growth and secondary metabolism, as a nonessential mechanism of plant life, also decreased by increasing exposure time, while SiO 2 NPs at 2 mg/l and ZnO NPs stimulated callus growth.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, BITC accumulation slightly increased in callus treated with 2 mg/l SiO 2 NPs for 45 days, while no changes were observed in 30-day-old callus treated with the same NP concentration. Similar findings were reported for the accumulation of thymol and carvacrol in thyme callus stressed with different concentrations of ZnO NPs [37]. By comparing the growth of callus with the accumulation of BITC, it was observed that due to the application of NPs at different concentrations, Fe 3 O 4 NPs at both concentrations and SiO 2 at 0.5 mg/l decreased the callus growth and secondary metabolism, as a nonessential mechanism of plant life, also decreased by increasing exposure time, while SiO 2 NPs at 2 mg/l and ZnO NPs stimulated callus growth.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, the concentration of Zn provided to plants should be precisely controlled for optimal plant development [ 24 ]. On the contrary, zinc oxide nanoparticles (ZnONPs) elicitation capability has been used to promote the production of bioactive secondary metabolites in medicinal plants [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employment of ENPs in the tissue/cell culture industry of medicinal plants is limited despite a lot of progress having been made in the last decade in the agricultural nanotechnology sector. The available literature suggests that ENPs evoke abiotic stress in tissue/cell culture raised medicinal plants [43][44][45][46][47][48]. These studies illustrate the effects induced by ENPs on the growth and secondary metabolism of plants of medicinal significance.…”
Section: Discussionmentioning
confidence: 92%